FAKTOR – FAKTOR YANG MEMPENGARUHI RISIKO INVESTASI SAHAM (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - lailatullatifa; MOCHAMMAD SHULTHONI (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2014)
The purpose of this study is to investigate and examine the factors that mempangaruhi risk investments in companies listed in Indonesia Stock Exchange is an interesting thing to do because of the nature of the risks that are always inherent in any investment, especially investment in common stock. This study uses secondary data collection techniques, to conduct library research and documentation. Secondary data were those used in this study were obtained from the official website of the Indonesia Stock Exchange and Bank Indonesia official website Companies sampled in this study amounted to 71-year study period from 2010 to 2012, the sampling technique used was purposive sampling. The data used are the financial statements and the Indonesian Capital Market Directory (ICMD). Data analysis techniques in this study using multiple regression, hypothesis testing method used is the coefficient of determination, simultaneous regression coefficient test, and test the partial regression coefficients, using the F-test and t-test at the 5% level of significance (α = 0.05 ). T test showed that capital structure has significant value equal to 0.05, financial leverage has a significant value below 0.05 is equal to 0.000, while the company's liquidity has a value of 0.019, meaning that the structure of capital, financial leverage, and liquidity of the company has significant influence against the risk of stock investing. While variable rate of inflation does not significantly above the value of 0.05 is 0.752. F test results indicate that the structure of capital, financial leverage, firm liquidity, and inflation effect on the risk of investment sim.